Trade Reform with Quotas, Partial Rent Retention, and Tariffs - Anderson, James E.; Neary, J. Peter (Econometrica, 1992)
Quotas are the predominant means of protection in developed countries, with quota rents commonly shared between exporter and importer. This paper derives shadow prices appropriate to evaluating trade reform under these circumstances and provides a number of useful sufficient conditions for welfare-improving "piecemeal" reform. In doing so, the authors apply the distorted (quantity-constrained) expenditure function and use implicit separability to derive more powerful results than have previously been available.